A low‐potential electrochemical method for fast development of latent fingerprints on brass cartridge cases by electrodeposition of poly(3, 4‐ethylenedioxythiophene). Issue 4 (31st August 2020) - Costa, Cristiane V.; Assis, Alexandro M. L.; Freitas, Johnnatan D.; Tonholo, Josealdo; Ribeiro, Adriana S.
Abstract: The electrodeposition of poly(3, 4‐ethylenedioxythiophene) (PEDOT) for development of latent fingerprints on brass cartridge cases may be successfully performed, even though the simultaneous corrosion process of copper and zinc from the brass surface occurs. PEDOT is electrodeposited by direct oxidation of the monomer in aqueous LiClO4 solution using chronoamperometry (potentiostatic method) with experimental conditions set at 0.90 V versus Ag/AgCl and 180 seconds. Such strategy is interesting for application in forensic biometrics for development of latent fingerprints on brass cartridge cases, since it affords images with high definition, allowing a clear visualization of the ridge patterns and singular points, besides to be useful for confrontation in fingerprint databases. Therefore, this is a simple, efficient, fast, low‐potential, and low‐cost methodology for the processing of cartridge cases. Abstract : PEDOT electrodeposition on brass cartridge cases is an effective strategy for development of latent fingerprints. The formation of a polymer film on brass surfaces allows for improved detection and visualization of fingerprint residues, providing high quality images for Forensic Biometrics, useful to identify an individual or even to establish a connection between crime scenes.